HUBUNGAN PENDIDIKAN DAN PELATIHAN DENGAN PRESTASI KERJA PEGAWAI PADA KANTOR DISTRIK NAVIGASI KELAS III SIBOLGA - Kartini Manurung, Yumiko Kanna (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Based on the research results obtained by the correlation coefficient obtained rxy = 0.79 shows the relationship of education and training with work performance there is a strong relationship. While the coefficient of determination obtained by 62.41% this means that the relationship of education and training with work performance is 62.41%. Simple linear regression obtained by the equation Y = 5.71 + 0.80X shows the relationship of education and training with positive work performance. Testing The t test can be concluded that education and training have a strong relationship with employee performance at the Sibolga Class III Navigation District Office, where tcount> ttable or 11.80> 1.989 is obtained. It is recommended that employees should take part in not only the training that is held within the organization, but also the training that is held from outside the organization so as to increase employee experience and facilitate employees in completing activities specifically related to public interests.